The Catalytic Performance of MnSO4-Doped Natural Zeolite in Ethyl Acetate Synthesis - Nugroho, Adelia Natasya Regita; Pambudi, Teguh; Alfieta Rohmaful Aeni; Retno Utami (Helium: Journal of Science and Applied Chemistry, 2025)
Ethyl acetate is a compound that is widely used across various industries. However, its esterification process typically requires a catalyst to improve reaction efficiency. This study focuses on developing a MnSO4-doped natural zeolite catalyst using the impregnation method to enhance its catalytic activity in the esterification of acetic acid and ethanol. The synthesized catalyst was characterized using FTIR, XRD, and SEM-EDS to analyze structural and morphological changes. FTIR characterization revealed the presence of Si-O-Si and Al-O-Si bonds in the 1000 to 1100 cm-1 region, while XRD confirmed that the zeolite with transition metal impregnation shows a decrease in the intensity of the diffraction peak. SEM-EDS analysis demonstrated that the MnSO4-doped natural zeolite exhibited a more uniform morphology, with manganese ions effectively integrated into the surface and pores of the zeolite. Additionally, EDS measurements detected the presence of elements such as Si, O, Al, Na, and Mn, confirming the successful modification of the zeolite to act as a catalyst. Catalytic testing showed that the highest ethyl acetate conversion achieved was 91.27% within 90 minutes, with optimal performance observed at a catalyst mass of 1 g. These findings indicate that modifying zeolite with MnSO4 can significantly enhance catalyst performance in esterification reactions, making it a more efficient and sustainable alternative to conventional catalysts.